Pengaruh Kinerja Keuangan Terhadap Harga Saham Pada Perusahaan Otomotif Di Bursa Efek Indonesia Periode 2012 – 2016 - Suri Mahrani (Universitas Mercu Buana, 2019)
The decline in the automotive industry's sales performance from 2012 to 2016 also affected the financial performance of the automotive industry. In 2015 PT. Goodyear Indonesia Tbk suffered a loss of US 353.76 thousand, PT. Astra Autopart Tbk also experienced the same thing. The decline in the automotive industry's sales performance from 2012 to 2016 also affected the financial performance of the automotive industry. Financial Performance Analysis is one technique to test whether financial information is useful to predict earnings growth or stock prices. Company sample data in this study for 5 years from 2012-2016. This research is to see the effect of financial performance on stock prices proxied on Dividend Per Share (DPS), Earning Per Share (EPS) and Return on Assets (ROA).